2018
DOI: 10.1590/1806-9282.64.08.717
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of survival in patients with brain metastases treated surgically: Impact of age, gender, oncologic status, chemotherapy, radiotherapy, number and localization of lesions, and primary cancer site

Abstract: SUMMARY OBJECTIVE To evaluate the survival of patients with brain metastases treated surgically according to the potentially involved factors. METHODS 71 patients treated surgically were analyzed with the diagnosis of brain metastases during the period from January 2011 to November 2014, totaling 47 months of follow-up. The Kaplan-Meier curve method was used for survival analysis. Results We evaluated 71 patients with brain metastases treated surgically, 44 female and 27 male, mean age of 60.1 years. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
2
12
3
2
Order By: Relevance
“…The frequency of metastatic cerebral tumors is increased due to improved systemic disease control, advanced imaging modalities, and increased use of routine screening for staging. a statistically significant prognostic effect on survival in this study despite previous publications (11). Finally, in a study with an enrollment of 71 subjects, Rotta et al reported that only gender affects survival, without any noticeable effects of age, histological type, KPS, location of cerebral metastases, and treatment type on survival (11).…”
Section: █ Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…The frequency of metastatic cerebral tumors is increased due to improved systemic disease control, advanced imaging modalities, and increased use of routine screening for staging. a statistically significant prognostic effect on survival in this study despite previous publications (11). Finally, in a study with an enrollment of 71 subjects, Rotta et al reported that only gender affects survival, without any noticeable effects of age, histological type, KPS, location of cerebral metastases, and treatment type on survival (11).…”
Section: █ Discussioncontrasting
confidence: 78%
“…a statistically significant prognostic effect on survival in this study despite previous publications (11). Finally, in a study with an enrollment of 71 subjects, Rotta et al reported that only gender affects survival, without any noticeable effects of age, histological type, KPS, location of cerebral metastases, and treatment type on survival (11). Similarly our results showed that surgically (metastasectomy) treated patients had similar outcomes and survival rates with those not treated with surgery.…”
Section: █ Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…A total of 78 patients with BM were eligble for this survival of BM patients in different setting . (9)(10)(11)(12)(13)(14)(15)(16) Several previous studies have shown that characteristic primary tumor and the treatment strategy before BM diagnosed was significant to the course of BM. (11.17) Lung cancer is the most common primary tumor and usually diagnosed at the same time of the diagnosed BM (synchronous).…”
Section: Resultsmentioning
confidence: 99%